The colostrum quality and composition of simmental and brown swiss heifers (Bioscience Journal, 2018)
The present study was conducted to determine the quality and composition of colostrum samples obtained from Simmental and Brown Swiss heifers on a Turkish dairy farm in Ã–demiÅŸ, Ä°zmir. The average volume of colostrum obtained from Simmental and Brown Swiss heifers at the first milking was 3.4 L and 3.8 L, respectively. Average colostrometer (Ig) and Brix values were determined as 105.1 mg/mL and 104.9 mg/mL, 29.97 % and 29.68 % of the samples (P>0.05). No significant differences were observed between colostrums' chemical compositionsâ€”including total solids, total protein, solids-not-fat, somatic cell counts (SCC), total bacterial counts (TBC), and energy values of the breeds - except for lactose concentration (P